The crystal structure of (E)-N′-(4-hydroxy-3-methoxybenzylidene)-2-naphthohydrazide monohydrate, C19H18N2O4 - Zhang Sheng-Ting; Zou Fei; Lai Ni; Yuan Lin; Li Zhong-Yan (Zeitschrift für Kristallographie - New Crystal Structures)
C19H18N2O4, monoclinic, P21/n (no. 14), a = 8.375(2) Å, b = 22.018(6) Å, c = 9.237(3) Å, β = 106.271(3)∘ $106.271{(3)}^{° }$ , V = 1635.1(8) Å3, Z = 4, Rgt ${R}_{gt}$ (F) = 0.0427, wRref ${wR}_{ref}$ (F 2) = 0.1185, T = 296(2) K.